Amiodarone for the treatment and prevention of ventricular fibrillation and ventricular tachycardia - Hugo Van Herendael; Paul Dorian (Vascular Health and Risk Management, 2010)
Hugo Van Herendael, Paul DorianDivision of Cardiology, St. Michael’s Hospital, University of Toronto, Toronto, CanadaAbstract: Amiodarone has emerged as the leading antiarrhythmic therapy for termination and prevention of ventricular arrhythmia in different clinical settings because of its proven efficacy and safety. In patients with shock refractory out-of-hospital cardiac arrest and hemodynamically destabilizing ventricular arrhythmia, amiodarone is the most effective drug available to assist in resuscitation. Although the superiority of the transvenous implantable cardioverter defibrillator (ICD) over amiodarone has been well established in the preventive treatment of patients at high risk of life-threatening ventricular arrhythmias, amiodarone (if used with a beta-blocker) is the most effective antiarrhythmic drug to prevent ICD shocks and treat electrical storm. Both the pharmacokinetics and the electrophysiologic profile of amiodarone are complex, and its optimal and safe use requires careful patient surveillance with respect to potential adverse effects.Keywords: amiodarone, ventricular fibrillation, unstable ventricular tachycardia